Transitioning from Medicaid to private health insurance: informing public and private sector outreach - White, Amy Samantha (Frontiers in Health Services, 2023)
This study explored the lived experiences of transitioning from Medicaid to private health insurance upon college graduation. Fifteen recent graduates of an urban, commuter, public college in the Mid Atlantic were interviewed via Zoom® to understand what they regard as crucial aspects of the transition experience, especially during the Covid pandemic. The subjects all identified as being members of a minority racial or ethnic group, the average age was 33 (SD = 10.96), and all but one interview subject majored in the health sciences. Every recent graduate reported experiencing difficulty in the transition. Subjects felt unprepared for the transition, alone, and without support. "Copays" was the most common response to questions, frequently said with arms in the air for emphasis, as if the word "copay" summarized all of the lack of preparation, difficulty, and expense of the health care system after previously receiving Medicaid (i.e., free health care). The findings inform how the private sector should on-board new college graduates. There is a need for Medicaid case officers to better prepare clients for the transition and for human resources personnel in the private sector to sufficiently explain how private health insurance works.